The Influence of Text-Based Learning and Independent Study Habits of Class VI Students at SDIT Generasi Muslim Cendekia (2023/2024) on Fiction Text Writing Skills - Suarni Suarni; Darmiany Darmiany; Saharudin Saharudin; Muhammad Sukri; Asrin Asrin (Lafadz Jaya Publisher, 2024)
This research aims to describe Text-Based Learning and Independent Study Habits of Class VI Students at SDIT Generasi Muslim Cendekia (2023/2024) regarding Fiction Text Writing Skills. This research is quantitative research, which can be interpreted as a type of research activity whose specifications are systematic, planned, and structured. Data analysis techniques in quantitative research use statistics. So, this research uses statistical inference. The results of the research hypothesis are accepted or there is a very strong influence on text-based learning on the skills of writing fiction texts in class VI at SDIT Generasi Muslim Cendekia. The hypothesis is rejected or there is no influence on text-based learning, independent study habits on fiction text writing skills in class VI at SDIT Generasi Muslim Cendekia. There is a very strong influence after implementing text-based learning on the skills of writing fiction texts in class VI at SDIT Generasi Muslim Cendekia. Increasing their knowledge through studying texts, especially the closest culture in the region of origin with the aim of being able to use it as a way to preserve the uniqueness of the region, can also be used as something of value for tourism, especially in the Central Lombok region.